BRAZILIAN HERNIA AND ABDOMINAL WALL SOCIETY STATEMENT ON LARGE HIATAL HERNIAS MANAGEMENT - Brandalise, André (2023)
Large hiatal hernias (LHH) besides being more prevalent in the elderly, have different clinical presentation: fewer reflux, more mechanical symptoms and a greater possibility of acute, life-threatening complications such as gastric volvulus, ischemia and visceral mediastinal perforation. Thus, surgical indications are distinct from gastroesophageal reflux disease (GERD-related), sliding hiatal hernias. Heartburn tends to be less intense, while symptoms of chest pain, cough, discomfort, and tiredness are reported more frequently. Complaints of vomiting and dysphagia may suggest the presence of associated gastric volvulus. Signs of iron deficiency and anemia are found. Surgical indication is still controversial and was previously based on high mortality reported in emergency surgeries for gastric volvulus. Postoperative mortality is especially related to three factors: body mass index (BMI above 35), age over 70 years and presence of comorbidity. Minimally invasive elective surgery should be offered to symptomatic individuals with good or reasonable performance status, regardless of age group. In asymptomatic and oligosymptomatic patients, besides obviously identifying the patient's desire, case-by-case analysis of surgical risk factors such as age, obesity and comorbidities, should be taken under consideration. One should also pay attention to situations with greater technical difficulty and risks of acute migration due to increased abdominal pressure (abdominoplasty, manual workers, spastic diseases). Technical alternatives such as partial fundoplication and anterior gastropexy can be considered. We emphasize the importance of performing surgical procedures in cases of LHH in high-volume centers, with experienced surgeons.